Evaluasi Program Pelaksanaan Sholat Dhuha Dalam Meningkatkan Kedisiplinan Siswa di SMP 2 Sungguminasa Kab. Gowa - W, Wahyudi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study evaluates the implementation of Dhuha prayer at SMP 2 Sungguminasa using the CIPP model (Context, Input, Process, Product). Through a qualitative approach, the research reveals that the Dhuha prayer activity conducted before class has successfully enhanced students' discipline and religious awareness. The support from teachers in motivating and supervising the activity plays a crucial role in its success. However, challenges such as limited facilities and a lack of awareness among some students remain. Overall, the program contributes positively to shaping students' spiritual character and discipline, with potential for improvement through more effective guidance and supervision.